2021
DOI: 10.1038/s41598-021-87235-6
|View full text |Cite
|
Sign up to set email alerts
|

Functional disability is related to serum chemerin levels in rheumatoid arthritis

Abstract: Adipokines, especially chemerin, can interact with cytokines and other molecules in inflammation. To date, there is insufficient information regarding a possible correlation between functional disability and chemerin and other pro-inflammatory molecules in rheumatoid arthritis (RA). To identify the association of functional disability with serum chemerin and other pro-inflammatory molecules, including other adipokines, cytokines and E-selectin, in patients with RA. Cross-sectional study. Assessment: disease ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 27 publications
2
4
0
Order By: Relevance
“…Similar to our findings, Herenius et al and Maijer et al also found a correlation with CRP [12,26]. Also consistent with these findings, our group previously reported that serum levels of chemerin were correlated with disability function in a small group of patients with RA [15].…”
Section: Plos Onesupporting
confidence: 93%
See 2 more Smart Citations
“…Similar to our findings, Herenius et al and Maijer et al also found a correlation with CRP [12,26]. Also consistent with these findings, our group previously reported that serum levels of chemerin were correlated with disability function in a small group of patients with RA [15].…”
Section: Plos Onesupporting
confidence: 93%
“…In early RA patients managed using the treat to target strategy, Tolusso et al identified that chemerin levels can be considered a predictor of early remission of inflammation [17]; however, other studies are required to validate these findings. These data published in the literature support the hypothesis that chemerin levels are related to disease activity in RA [11,15,18]. Nevertheless, there are no previous studies assessing the relation between the persistence of disease activity in RA patients treated with DMARDs and serum chemerin levels.…”
Section: Introductionsupporting
confidence: 77%
See 1 more Smart Citation
“…Multivariable analysis confirmed association with IMT. Chemerin was previously correlated with disease activity, BMI, CRP, RF, ESR and CCP [ 67 , 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…In an observational cross-sectional study, Vazquez-Villegas et al [ 163 ] evaluated the chemerin serum levels and the occurrence of functional disabilities among women with RA. In all, data from 82 patients (35–75 years old) were analyzed, and 43 of them presented at a minimum of one functional affection.…”
Section: General Aspects Of Ra and The Role Of Myokines Osteokines Ad...mentioning
confidence: 99%